Transformasi Pendidikan Islam di Era Digital dan Globalisasi: Mengintegrasikan Tech, Touch, Dan Teach - Ibrahim, Ende; Intania, Naila; Mansur (Paedagogie, 2026)
Islamic education stands at a crossroads between deeply rooted pedagogical traditions and the urgent demands of digital transformation and globalization. This article examines how Islamic educational institutions can constructively respond to these challenges through an integrative framework that weaves together three core dimensions: technology utilization (Tech), the preservation of meaningful personal interaction (Touch), and the application of adaptive pedagogical methods (Teach). Drawing on a qualitative literature study approach focused on Scopus-indexed international journal publications from 2020-2025, this article identifies transformation patterns, implementation challenges, and best practices proven effective in enhancing the quality of Islamic education. Findings reveal that these three dimensions are not alternatives that replace one another, but rather complementary elements that must be synergistically integrated to produce a holistic learning ecosystem that is spiritually grounded and responsive to the needs of the digital generation.